Electrospun meshes possessing region‐wise differences in fiber orientation, diameter, chemistry and mechanical properties for engineering bone‐ligament‐bone tissues. Issue 12 (26th September 2014) - Samavedi, Satyavrata; Vaidya, Prasad; Gaddam, Prudhvidhar; Whittington, Abby R.; Goldstein, Aaron S.
ABSTRACT Although bone‐patellar tendon‐bone (B‐PT‐B) autografts are the gold standard for repair of anterior cruciate ligament ruptures, they suffer from drawbacks such as donor site morbidity and limited supply. Engineered tissues modeled after B‐PT‐B autografts are promising alternatives because they have the potential to regenerate connective tissue and facilitate osseointegration. Towards the long‐term goal of regenerating ligaments and their bony insertions, the objective of this study was to construct 2D meshes and 3D cylindrical composite scaffolds – possessing simultaneous region‐wise differences in fiber orientation, diameter, chemistry and mechanical properties – by electrospinning two different polymers from off‐set spinnerets. Using a dual drum collector, 2D meshes consisting of an aligned polycaprolactone (PCL) fiber region, randomly oriented poly(lactide‐co‐glycolide) (PLGA) fiber region and a transition region (comprised of both PCL and PLGA fibers) were prepared, and region‐wise differences were confirmed by microscopy and tensile testing. Bone marrow stromal cells (BMSCs) cultured on these meshes exhibited random orientations and low aspect ratios on the random PLGA regions, and high aspect ratios and alignment on the aligned PCL regions. Next, meshes containing an aligned PCL region flanked by two transition regions and two randomly oriented PLGA regions were prepared and processed into 3D cylindrical composite scaffolds using an interpenetrating photo‐crosslinkable polyethylene glycol diacrylate hydrogel to recapitulate the shape of B‐PT‐B autografts. Tensile testing indicated that cylindrical composites were mechanically robust, and eventually failed due to stress concentration in the aligned PCL region. In summary, this study demonstrates a process to fabricate electrospun meshes possessing region‐wise differences in properties that can elicit region‐dependent cell responses, and be readily processed into scaffolds with the shape of B‐PT‐B autografts. Biotechnol. Bioeng. 2014;111: 2549–2559. © 2014 Wiley Periodicals, Inc.